A construção de conceitos de ciências naturais na educação infantil - Martins, Lilian Cassia Bacich (2008)
The aim of the present research was to verify if 5 years old students, attending pre-school, can establish relationships between the concepts of hygiene , health and microbes , which were previously worked through participation in an experiment mediated by the researcher. The Socio-historical theory in Psychology provided support for data analyses. All data was collected through activities that took place in the proper educational context of the students, respecting the social and cultural milieu provided by the school. Initially, in order to recognize the children s everyday concepts, a story in which the main character was Cascão, a member of Monica s group was told; it was followed by an experiment at the school s lab, which main focus was the development of microorganisms colonies. Finally, a follow-up was completed, making use of comic strips from Monica s group comic story. The results showed that a conceptual advance had happened, being incorporated in children s choices and decisions. Since the pupils had established relations among the studied concepts, the conclusion pointed out that if it is possible to promote conceptual changes in the subjects, this does not imply the elaboration of scientific concepts themselves. In fact, this must not be intended to, since the ZRD of the children do not allow so